(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2024)
To date, the countries of Central Asia - Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan and Uzbekistan have great potential for regional industrial cooperation and are interested in developing this cooperation. For these countries with a rich history and diverse resources, the development of economic integration and cooperation has a strategic position, and high profitability can be achieved by launching new projects. Strengthening regional ties will help to diversify the economy, increase competitiveness and attract foreign investments. This article examines the current landscape of industrial cooperation in Central Asia, highlights opportunities for development, and analyzes the challenges to be overcome.